2019
DOI: 10.1016/j.ebiom.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of vimentin reduces mesenchymal phenotype of cholangiocytes in the Mdr2−/− mouse model of primary sclerosing cholangitis (PSC)

Abstract: BackgroundCholangiocytes are the target cells of cholangiopathies including primary sclerosing cholangitis (PSC). Vimentin is an intermediate filament protein that has been found in various types of mesenchymal cells. The aim of this study is to evaluate the role of vimentin in the progression of biliary damage/liver fibrosis and whether there is a mesenchymal phenotype of cholangiocytes in the Mdr2−/− model of PSC.MethodsIn vivo studies were performed in 12 wk. Mdr2−/− male mice with or without vimentin Vivo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
(72 reference statements)
3
21
0
Order By: Relevance
“…We found that cholangiocytes showed a notable enrichment by PBC-relevant genetic association signals (Permuted P < 0.05, Figure 3b and Supplemental Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC 44,45 .…”
Section: Resultssupporting
confidence: 93%
“…We found that cholangiocytes showed a notable enrichment by PBC-relevant genetic association signals (Permuted P < 0.05, Figure 3b and Supplemental Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC 44,45 .…”
Section: Resultssupporting
confidence: 93%
“…( 42 ) Other correlative assessments regarding α‐CGRP, SCF, or vimentin levels were carried out in PSC human tissue to confirm the preclinical data obtained in rodents, as previously described. ( 49 , 50 , 51 ) Finally, increased levels of twinfilin‐1 were detected in cholangiocytes of patients with PBC or PSC. This protein, in experimental cholestasis, appeared to respond to several microRNA signals and to play a major role in supporting the proliferative/senescent evolution of bile duct cells in this setting.…”
Section: Aging Of the Biliary Epitheliummentioning
confidence: 95%
“…Its inhibition improves biliary damage and cellular senescence, possibly interfering with the epithelial to mesenchymal transition (EMT) process of bile duct cells, a mechanism linked to the onset of fibrosis. ( 51 ) Finally, the direct targeting of senescent cellular machinery has been attempted, in experimental systems, to improve pathological features. Inhibition of the cyclin‐dependent kinase inhibitor p16 has been obtained in a model of cholestasis by the administration of p16 morpholino.…”
Section: Aging Of the Biliary Epitheliummentioning
confidence: 99%
“…A growing body of literature indicates that vimentin controls cell proliferation (Cheng 2016). Extensive research in vimentin-de cient animal models (for example, vim −/− mice) showed that loss of vimentin caused a reduction in brosis and the mesenchymal phenotype of cells (for example, in cholangiocytes), which could be reversed upon vim re-expression (Eckes 1998;Zhou 2019). In contrast, some oncogenes could increase cell proliferation, as a result of a higher vimentin messenger RNA (mRNA) and protein levels (Rathje 2014).…”
Section: Introductionmentioning
confidence: 99%